Developmental changes of bodily self-consciousness in adolescent girls - Raoul, Lisa; Goulon, Cédric; Sarlegna, Fabrice; Grosbras, Marie-Hélène (Scientific reports, 2024)
The body and the self change markedly during adolescence, but how does bodily self-consciousness, the pre-reflexive experience of being a bodily subject, change? We addressed this issue by studying embodiment towards virtual avatars in 70 girls aged 10–17 years. We manipulated the synchrony between participants’ and avatars’ touch or movement, as well as the avatar visual shape or size relative to each participant’s body. A weaker avatar’s embodiment in case of mismatch between the body seen in virtual reality and the real body is indicative of a more robust bodily self-consciousness. In both the visuo-tactile and the visuo-motor experiments, asynchrony decreased ownership feeling to the same extent for all participants, while the effect of asynchrony on agency feeling increased with age. In the visuo-tactile experiment, incongruence in visual appearance did not affect agency feeling but impacted ownership, especially in older teenage girls. These findings highlight the higher malleability of bodily self-consciousness at the beginning of adolescence and suggest some independence between body ownership and agency.